2000
DOI: 10.1161/01.hyp.36.6.952
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Assessment of the Digital Volume Pulse

Abstract: Abstract-The digital volume pulse can be recorded simply and noninvasively by photoplethysmography. The objective of the present study was to determine whether a generalized transfer function can be used to relate the digital volume pulse to the peripheral pressure pulse and, hence, to determine whether both volume and pressure pulse waveforms are influenced by the same mechanism. The digital volume pulse was recorded by photoplethysmography in 60 subjects (10 women, aged 24 to 80 years), including 20 subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
111
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 255 publications
(113 citation statements)
references
References 22 publications
1
111
0
1
Order By: Relevance
“…It has been stated that the DVP obtained by photoplethysmography and pressure pulse waveforms assessed by tonometry have a complex relation that is not fully understood. 24 In this study, active smoking and BMI were factors independently associated with the SI, whereas arterial hypertension and cholesterol level were the independent determinants of the aortic AIx.…”
Section: Discussionmentioning
confidence: 49%
“…It has been stated that the DVP obtained by photoplethysmography and pressure pulse waveforms assessed by tonometry have a complex relation that is not fully understood. 24 In this study, active smoking and BMI were factors independently associated with the SI, whereas arterial hypertension and cholesterol level were the independent determinants of the aortic AIx.…”
Section: Discussionmentioning
confidence: 49%
“…26,27 Currently, the most popular method for evaluating arterial stiffness is obtained by estimating the pulse transit time between the carotid and femoral arteries using the tonometric technique. 8,19 This technique gives a reliable index of the regional AoStiff, 28,29 but represents only an estimate of the local AoStiff because it is a summation of the individual biomechanical properties of different arterial walls (that is, carotid, aorta, iliac and femoral arteries) located between the two recording sites.…”
Section: Discussionmentioning
confidence: 99%
“…This device estimates the SI by analyzing the photoplethysmographic waves (digital volume pulse) acquired on the fingertip of the subject. 23 The determining form of SI is shown in Figure 2. All statistical analyses were performed using the NCSS Statistical software.…”
Section: Reference Methodsmentioning
confidence: 99%
“…[18][19][20][21][22] A surrogate of PWV, the stiffness index (SI), has also been proposed by assessing capillary consequences of arterial stiffness using photoplethysmography, although some studies have showed a feeble correlation between SI and carotid-femoral PWV (PWV cÀf ). [23][24][25] The calculation of propagation time can be measured by various means, including analyzing the foot of the pulse wave, the points of maximum upslope or peak-to-peak time.…”
Section: Introductionmentioning
confidence: 99%